Schooling and the distribution of wages in the European private and public sectors - Budría, Santiago (2015)
International research has shown that schooling enhances within-groups wage dispersion. This assessment is typically based on private sector data and, up to date, the inequality implications of schooling have not been documented for the public sector. This paper uses recent data from eight European countries to explicitly take into account differences between the private and public sectors. Using quantile regression, the paper describes the effects of schooling on the location and shape of the conditional wage distribution in each sector. While the average impact of schooling on wages is similar across sectors, the impact of schooling on within-groups dispersion is found to be substantially larger in the private sector than in the public sector. This finding warns that the effects of the European educational expansion on overall within-groups dispersion may be lower than previously thought.